Theoretical and Numerical Investigation of Reduction of Viscous Friction in Circular and Non-Circular Journal Bearings Using Active Lubrication - Denis Shutin; Yuri Kazakov (Lubricants, 2023)
Reducing friction losses is one of the most common ways to improve fluid film bearings, whose adjustable design provides additional opportunities to improve their dynamic and tribological properties. Previous studies have shown the possibility of reducing viscous friction in actively lubricated bearings by adjusting the rotor position. This work provides a theoretical justification for the mechanism of this effect for the cases of purely laminar lubricant flows in journal bearings. The operating modes connected with the transition to turbulent phenomena and the occurrence of Taylor vortices are beyond the scope of this paper. Conditions that ensure the minimization of friction losses in hydrodynamic and hybrid bearings with hydrostatic parts are determined based on the equations describing viscous friction in a fluid film. In non-adjustable plain hydrodynamic bearings, the minimum of friction is achieved with the centered shaft position that is actually unstable due to the resulting forces configuration. In actively lubricated hybrid bearings, a further reduction in viscous friction is possible by combining film thickness and pressure distributions. Recombining them, along with adjustment of the shaft position, allows the optimization of the distribution of shear stresses in the fluid film. As a result, the shear stresses caused by the rotation of the shaft can be partially compensated by the stresses caused by the pressure gradient, reducing the torque-resisting rotation. In addition, additional benefits can be obtained in the minimum friction state by the reduced lubricant flow and power losses to its pumping. A series of numerical calculations for elliptical, 3-, and 4-lobe bearings show that non-circular bores provide additional variability in film thickness distribution and a premise for optimizing the bearing tribological parameters. Four-lobe bearing demonstrated the best ability for reducing viscous friction among the considered designs. The results obtained can be used as a basis for further optimization of the geometry of fluid film bearings of both active and passive designs by reducing power losses due to viscous friction.